Hebrew Medical Manuscripts in Portugal between the 13th and the 16th centuries - Visan, Irina (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
Portugal has been an important Jewish intellectual center in the Middle Ages and during the 16th century. The Hebrew manuscripts that survive from this period testify to the prosperity of the Jewish community in different fields such as philosophy, language and grammar, medicine, astro-medicine, pharmacology. This article describes the context of production of the Hebrew medical manuscripts between the 13th and the 16th centuries and it looks at the uncertainty that hovers over the exact number of Hebrew medical manuscripts that were written in Portugal during this period. The article explores the catalogue of the Hebrew manuscripts at the Jewish National and University Library in Jerusalem and provides a list of seven scientific Hebrew manuscripts that were written in Portugal between the 13th and the 16th centuries, three of which being medical manuscripts or concerning medical issues. Furthermore, this article is a call to explore the Hebrew medical manuscripts and to analyze their content.